City service station: developing the public amenity network for the new urban community - Hausler, Kay (My University, 2011)
The inner city of Johannesburg has encountered many changes in its identi ty, use and level of occupati on. In 2010, downtown Johannesburg is comprised of pockets of vibrant acti on and producti on with an ever-increasing industrious populace and residenti al sector, and therefore ever-increasing pressure on the public services. With the legal and illegal conversion of countless commercial buildings for housing, what is apparent is the lack of basic public ameniti es. While the informal network, clustering around populated points, sati sfi es minor daily needs, its transient, simplisti c, repeti ti ve system, does not perform to the extent required by a residenti al community. These enterprises are neither large enough to be an insti tuti on, constant enough to be socially inclusive nor structured enough to be capable of fulfi lling social services. Concurrently, there exists a series of unuti lised, unproducti ve private spaces; a dormant network of sites, saturated with potenti al to fulfi l that which the city is lacking, an effi cient public territory. [ Taking something the city has and doesn’t need and creati ng something city dwellers don’t have, and need. ] This thesis aims to use unproducti ve ‘gaps’ to create a model for urban public infi ltrati on; incorporati ng existi ng ameniti es into a complex, hybridised, democrati c structure. The result is to be the formati on of an inclusive social service network, provision of basic ameniti es, opportuniti es for the gathering of an increasing residenti al populati on and the recepti on and integrati on of a non-residenti al and immigrant populati on, in the city of Johannesburg.